2016
DOI: 10.1186/s12889-016-3275-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of hypertension in Myanmar - a nationwide cross-sectional study

Abstract: BackgroundNon-communicable diseases (NCDs), malaria and tuberculosis dominate the disease pattern in Myanmar. Due to urbanization, westernized lifestyle and economic development, it is likely that NCDs such as cerebrovascular disease and ischemic heart disease are on a rise. The leading behavioral- and metabolic NCDs risk factors are tobacco smoke, dietary risks and alcohol use, and high blood pressure and body mass index, respectively. The study aimed at estimating the prevalence and determinants of hypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
47
5
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 22 publications
14
47
5
2
Order By: Relevance
“…As compared with national data from 2009 (30%) [14, 15], the prevalence of hypertension is higher in both urban and rural Yangon. Studies have reported that salt-intake in South-East Asian countries is high [42], and because salt and mono-sodium glutamate (MSG) intake are associated with high blood pressure [4345], they could be a contributor to high prevalence of hypertension in Myanmar.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…As compared with national data from 2009 (30%) [14, 15], the prevalence of hypertension is higher in both urban and rural Yangon. Studies have reported that salt-intake in South-East Asian countries is high [42], and because salt and mono-sodium glutamate (MSG) intake are associated with high blood pressure [4345], they could be a contributor to high prevalence of hypertension in Myanmar.…”
Section: Discussionmentioning
confidence: 91%
“…Similar to other figures from the region [34], daily smoking prevalence in males outnumber females, more than ten times in urban area and about three and a half time in rural area. The overall prevalence of smokeless tobacco (28.0% for urban areas and 32.5% for rural areas) is comparative to the 2009 nationwide figure (30.0%) [14, 15]. The results indicate that in both urban and rural areas, tobacco consumption among males stands as a public health problem in Myanmar, although more than 90% of smokers consumed less than ten tobacco units (cigarettes or cheroots) daily Tobacco use is a socio-culture entertaining habit in this society [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] In Asia, prevalence of hypertension between the years 2008 and 2015 has been largely similar to the global average. Nationwide surveys have found prevalence to be 48.3% in Brunei, [14] 15.3% in Cambodia, [15] 33.4% in Indonesia, [16] 24.9% among men and 20% among women in Laos, [17] 35.3% in Malaysia, [18] 31% in males and 29% in females in Myanmar, [19] 23.5% in Singapore, [20] 19.1% in Thailand, [21] and 25.1% in Vietnam. [22] Trends in hypertension prevalence have not been consistent across SEA nations.…”
Section: Trends In Hypertension Prevalencementioning
confidence: 99%
“…Awareness of prior diagnosis of hypertension also varies widely between the Southeast Asian nations. Awareness of hypertension is highest in Singapore at 73.7%, [20] followed by Thailand and Vietnam at 48.4%, [21,22] and lowest in Myanmar at 27.8%, [19] while awareness to hypertension has increased in Asian countries such as Indonesia, Malaysia, Myanmar, and Singapore levels still fall far short of awareness levels in Western nations such as the US (81%), Canada (83%), and England (65%). [28]…”
Section: Awareness Of Hypertensionmentioning
confidence: 99%